Las fabulaciones de nuestra realidad. Apuntes para una poética del grupo leonés de J. P. Aparicio, L. M. Diez y J. M. Merino - Brizuela, Mabel (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2003)
The Juan Pedro Aparicio (1941), Luis Mateo Díez (1942) and José María Merino's (1941) "Grupo leonés" makes its appearance among what has been called in contemporary Spanish narrative "generación del 68", sprouted round about the "filandón" with a strong fascination for the oral tradition tales and the commitment to the recovery of narrativity. Though each of them had explored such different literary worlds, their connection point is a space that belongs to everybody's memory, and a common apocryphal character: Sabino Ordás, "patriaren of León's literature". These writers have produced, besides apocryphal, and at the same time they produced their fíctional work, a lavish material of critical reflection. Between metatextual and narrative speech a strong articulation is revealed, and their mechanisms and strategies allow us to state a León's narrative's poetics.